THE IMPACT OF VISIONARY LEADERSHIP, LEARNING ORGANIZATION AND INNOVATIVE BEHAVIOR TO PERFORMANCE OF CUSTOMS AND EXCISE FUNCTIONAL - Muhammad Anshar (Program Studi S3 Ilmu Manajemen, 2017)
This research aims to determine the impact of visionary leadership, learning organization, and innovative behavior on the performance of Functional Officers of Customs and Excise Inspectors at Tanjung Priok Customs and Excise Main Service Office. The research was conducted at Tanjung Priok Customs and Excise Service Office using the number of samples of 78 Functional Officers of Customs and Excise Inspectors. The sample was selected using simple random sampling technique. Data collection was done by using questionnaire and data analysis using path analysis. The results showed that 1) visionary leadership, learning organization and innovative behavior have a direct and positive impact on performance, 2) visionary leadership, and learning organization have a direct and positive impact on innovative behavior and 3) visionary leadership have a direct and positive impact on learning organization. The conclusion of this research is to improve the performance of Functional Officer of Customs and Excise Inspectors at TanjungPriok Customs and Excise Main Service Office, it is necessary to increase the aspect of visionary leadership from Head of Main Service Office, learning organization at Main Service Office and innovative behavior at Functional Officers of Customs and Excise Inspectors. Keywords : visionary leadership, learning organization, innovative behavior, and Performance.